The evolution of Cochrane evidence summaries in health communication and participation: seeking and responding to stakeholder feedback. (1st June 2018) - Synnot, Anneliese J; Lowe, Dianne; Merner, Bronwen; Hill, Sophie J
Abstract : Knowledge translation resources that summarise and disseminate systematic review findings can support evidence into policy and practice. Since 2007, we have produced Evidence Bulletins; brief, web-based summaries of Cochrane Reviews published by Cochrane Consumers and Communication. Evidence Bulletins are designed for health decision makers employed by or in representational roles within policy and practice settings, that is, policy makers, health professionals and consumer and carer representatives. In this paper, we describe the evolution of our Evidence Bulletins, including revisions made to ensure they reflect the latest research-based guidance on evidence summaries, the results of a subsequent evaluation, and how we incorporated the evaluation findings by making further revisions to the Evidence Bulletin development process and format. The main initial revision to the Evidence Bulletins was the addition of a new section, in which we explicitly considered the relevance of the evidence to the healthcare context in Victoria, Australia. To evaluate the Bulletins, we conducted structured feedback sessions at five Australian health services involving 14 staff and eight consumer representatives. Participants were invited to share their perceptions about the usefulness of the Bulletins and how they might use them for decision making. Although the Evidence Bulletin format, and the new Relevance section were broadly endorsed by both stakeholder groups, a number of suggestions for improvement were identified. As preferences varied somewhat between the two groups; specifically identifying the intended audience for each Bulletin and seeking the input of the nominated stakeholder group in the development may improve usefulness.Key messages Health service staff and consumer representative preferences for evidence summary formats and content can differ. Evidence summary usefulness and relevance can be enhanced by feedback and partnering with stakeholders in development. More detail about populations, setting and interventions may be needed to for stakeholders to consider local relevance.